Multidimensional Plasma Lipids Affect Preeclampsia/Eclampsia: A Mendelian Randomization Study - Shi, Shaole; Wu, Fangyuan; Zhao, Shanshan; Wang, Zilian; Fan, Yongqiang (The journal of clinical hypertension (Greenwich, Conn.), 2025)
ABSTRACT Circulating lipids play a crucial role during pregnancy and may impact various pregnancy‐related diseases. This study employed a two‐sample Mendelian randomization (MR) framework to investigate the causal relationship between alterations in multidimensional plasma lipid levels and the risk of preeclampsia or eclampsia, offering deeper insight into this association. The inverse variance weighted (IVW) method was utilized as the main analysis. Summary statistics from plasma lipidomics of 7174 Finnish individuals and summary data on preeclampsia/eclampsia from the FinnGen consortium involving 219 817 European participants were employed. Sensitivity analyses were conducted to evaluate heterogeneity and pleiotropy. The study identified 17 lipid species from a total of 179 lipid species associated with susceptibility to preeclampsia/eclampsia. Notably, ten species, including six triacylglycerols (TAGs) (50:1, 48:1, 56:4, 49:2, 48:2, 54:3), a diacylglycerol (DAG) (16:1_18:1), and three sphingomyelins (SMs) (d36:1, d34:1, d38:1), were found to increase the risk of preeclampsia/eclampsia. Conversely, seven species, including five phosphatidylcholines (PCs) (16:1_20:4, O‐18:1_20:4, 18:1_20:4, 16:0_20:4, 17:0_20:4) and two phosphatidylethanolamines (PEAs) (18:0_20:4, 16:0_20:4), all containing arachidonic acid (ARA) in the sn‐2 position, were associated with a reduced risk of preeclampsia/eclampsia (all p < 0.05). The results of the stratified analysis were consistent with these findings. Furthermore, reverse MR analysis indicated that preeclampsia/eclampsia does not causally affect plasma levels of these lipids. Our findings established a causal relationship between specific plasma lipid species and modulation of preeclampsia/eclampsia risk, providing improved resolution for risk assessment and potential therapeutic targets in the disease.